THE IMPACT OF SUFIS ON ACTIVATING THE JIHAD MOVEMENT AGAINST THE CRUSADERS DURING THE ERA OF SALADIN - Kadro, Narjes (Veredas do Direito, 2026)
The concept of Sufism has been the subject of varying opinions, with diverse perspectives on its origins and historical development. Despite the criticisms leveled against Sufism by some scholars, its significant role in confronting external threats and calling Muslims to jihad cannot be denied. This study highlights the importance of Salah al-Din's engagement with Sufis and their role in encouraging people to resist the Crusaders. It also sheds light on Salah al-Din's notable efforts to support Sufis by establishing institutions for their benefit. The research begins by defining Sufism, exploring its early spread within Islamic civilization, examining the origins of the concept, and analyzing the reasons behind the Sufis’ inclination towards seclusion. It further investigates their preference for residing in ribats (fortified structures on the frontiers established to protect Muslim borders) and the ways rulers, particularly during the Ayyubid era, utilized their influence. Additionally, the study examines prominent Sufi figures during Salah al-Din's time and discusses key Sufi institutions of the period, such as the Salahiyya Khanqah and the Khanqah of Sa'id al-Sa'da. The research concludes by presenting key findings, including Salah al-Din's strategic use of Sufis to confront the Crusader threat and their critical contribution to the spiritual preparation of Muslims, culminating in the liberation of Jerusalem.